Influence of the bordering shelves on nutrient distribution in the Arctic halocline inferred from water column nitrate isotopes. (13th July 2018) - Fripiat, F.; Declercq, M.; Sapart, C. J.; Anderson, L. G.; Bruechert, V.; Deman, F.; Fonseca‐Batista, D.; Humborg, C.; Roukaerts, A.; Semiletov, I. P.; Dehairs, F.
Abstract: The East Siberian Sea and contiguous western Arctic Ocean basin are characterized by a subsurface nutrient maximum in the halocline, generally attributed to both Pacific inflow and intensive remineralization in shelf bottom waters that are advected into the central basin. We report nitrogen and oxygen isotopic measurement of nitrate from the East Siberian Sea and western Eurasian Basin, in order to gain insight into how nitrate is processed by the microbial community and redistributed in the Arctic Ocean. A large decoupling between nitrate δ 15 N and δ 18 O is reported, increasing and decreasing upward from the Atlantic temperature maximum layer toward the surface, respectively. A correlation between water and nitrate δ 18 O indicates that most of the nitrate (> 60%) at the halocline has been regenerated within the Arctic Ocean. The increase in nitrate δ 15 N correlates with the fixed N deficit, indicating a causal link between the loss of fixed N and the 15 N enrichment. This suggests that a significant share of benthic denitrification is driven by nitrate supplied by remineralization and partial nitrification, allowing residual 15 N‐enriched ammonium to diffuse out of the sediments. By increasing nutrient concentrations and fixed N deficit in shelf bottom waters, this imprint is attenuated offshore following advection into the halocline by nitrate regeneration and mixing. Estimation of the sedimentary isotope effect related to benthic denitrification yields values in the range of 2.4–3.8‰, with its magnitude driven by both the degree of coupling between remineralization and nitrification, and fixed N concentrations in shelf bottom waters.